THE IMPACTS OF SPEAKING ANXIETY ON STUDENTS’ LEARNING PROCESS - Najla Annisa Zuhri; Kisman Salija; Geminastiti Sakkir (Universitas Negeri Makassar, 2022)
This study aims to determine the level of student anxiety from the factors that cause anxiety and the impact of speaking anxiety on the student learning process at SMA Negeri 1 Parepare. This research applied mixed methods research design. The data were collected from the questionnaire and interview. The subjects of this study were second-grade students in science and social students. The questionnaire was conducted on 96 students and the interview was conducted on 9 students. Based on data analysis, it was found that the percentage of the Foreign Language Class Anxiety Scale (FLCAS) questionnaire on internal and external factors of students' speaking anxiety in the learning process was 1 student (1,04%) at a very anxious level and 10 students (10.42%) at the level of anxiety. while the other 59 students (61.46%) were at a mildly level of anxiety. 23 students (23.96%) were at the relaxed level, and 3 students (3.13%) were at the very relaxed level. The results of this study indicate that the average score of students' speaking anxiety as a whole is at a mild level of anxiety, with an average score of 78.43. The impact of speaking anxiety on the student's learning process is due to the low motivation of students to learn in English, lack of vocabulary, lack of knowledge of grammar, lack of pronunciation, never having practiced speaking in English, lack of opportunity to speak in front of crowds, and nervousness. This has a negative impact on students by causing them to be blank, stuttering, afraid, nervous, and anxious.